2012
DOI: 10.5937/ratpov49-1173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave heating on content of cyanogenic glycosides in linseed

Abstract: Summary: Linseed is a good source of linoleic (LA, 18:2, n-6) and especially α-linolenic acid (ALA, 18:3, n-3), ω6 and ω-3 polyunsaturated fatty acids (PUFA), which are essential because mammals, and therefore humans, cannot endogenously synthesize them and must adopt them exogenously from dietary sources. In spite of its high nutritive value, linseed has not been effectively exploited in animal feeding, due to the fact that it contains antinutritive components, which are cyanogenic glycosides (CG) and antivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…This trend was seen across the board in all replicate experiments. These findings are similar to the study results by [25]. According to this study, linseed was macerated for 120 to 240 min to release HCN.…”
Section: Optimisation Of Maceration Time and Temperature And Recovery...supporting
confidence: 91%
See 1 more Smart Citation
“…This trend was seen across the board in all replicate experiments. These findings are similar to the study results by [25]. According to this study, linseed was macerated for 120 to 240 min to release HCN.…”
Section: Optimisation Of Maceration Time and Temperature And Recovery...supporting
confidence: 91%
“…These results suggest that the optimum temperature for the maximum HCN release is 30 °C. These findings are similar to the study results by [25]. According to this study, linseed was macerated for 120 to 240 min to release HCN.…”
Section: Optimisation Of Maceration Time and Temperature And Recovery...supporting
confidence: 91%
“…Dusica et al . () investigated effect of microwave treatment on the content of cyanide and the loss of cyanide was 25.0%, that the content of cyanide at level of 243 mg kg −1 of flaxseed. Wu et al .…”
Section: Resultsmentioning
confidence: 99%
“…Yazıcı et al (2007) found that the loss of cyanide from solutions using ultrasonic waves was 25.0% at the highest level of ultrasonic intensity of 114 W cm À2 for the treatment of the effluents, while this treatment was time-consuming and tedious. Dusica et al (2012) investigated effect of microwave treatment on the content of cyanide and the loss of cyanide was 25.0%, that the content of cyanide at level of 243 mg kg À1 of flaxseed. Wu et al (2008) reported that the loss of cyanide was 83.3% when the extrusion treatment on flaxseed was investigated via uniform design optimisation, which had a complicate and difficult to control operation.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation